1997
DOI: 10.1111/j.1365-2052.1997.00096.x
|View full text |Cite
|
Sign up to set email alerts
|

A partially deficient and atypical equine transferrin variant, TF N

Abstract: A new, partially deficient and phenotypically atypical transferrin variant, TF N, was detected in sera of a number of Finnhorses belonging to one family. The variant was inherited codominantly. In polyacrylamide gel electrophoresis (pH 9.0) of sera, variant N appeared as a single weak band migrating slightly faster than the main anodal band of variant M. After immunoblotting or isolation an additional, still weaker, faster band was observed as well as some trace bands. The cathodal component, which is present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…An asymmetric ratio of the Tf C 1 and D 2 variants (faint tetrasialo-isoform D in contrast to tetrasialo-Tf C) was noted in the native sample, as well as after the digestion by neuraminidase (weak asialo-isoform D band) in one patient; the change of the amino acid sequence in the protein of the rare Tf D 2 variant might result in changes of immunodetection specificity. Similar asymmetry in serum aAT M/Z and M/S variants is well known (Jeppsson and Franzén 1982); unequal expression of some Tf alleles in the horse has also been reported (Niini et al 1997).…”
Section: Figuresupporting
confidence: 67%
“…An asymmetric ratio of the Tf C 1 and D 2 variants (faint tetrasialo-isoform D in contrast to tetrasialo-Tf C) was noted in the native sample, as well as after the digestion by neuraminidase (weak asialo-isoform D band) in one patient; the change of the amino acid sequence in the protein of the rare Tf D 2 variant might result in changes of immunodetection specificity. Similar asymmetry in serum aAT M/Z and M/S variants is well known (Jeppsson and Franzén 1982); unequal expression of some Tf alleles in the horse has also been reported (Niini et al 1997).…”
Section: Figuresupporting
confidence: 67%
“…The three putative mutations at the TF locus resulted in three variants designated D* that were electrophoretically indistinguishable at pH 7.9 (Fig. Niini et al (1994) reported in Finn horses a new partially deficient and phenotypically atypical transferrin variant, N, which was inherited co-dominantly. Five additional mutations produced F,*, which migrated between D* and D; H*.…”
Section: Resultsmentioning
confidence: 99%
“…case 4, O+F1*). Niini et al (1994) reported in Finn horses a new partially deficient and phenotypically atypical transferrin variant, N, which was inherited co-dominantly. This variant lacked the cathodal minor two sialic acid residue component that is present in other TF variants (Strati1 et al.…”
Section: Resultsmentioning
confidence: 99%
“…(5) A hypoglycosylation defect on a rare Tf D variant, when replacement of amino acid involves one of the branching positions resulting in a loss of the entire carbohydrate chain; such an abnormal hypoglycosylated Tf variant was found among the Japanese and New Zealand populations (17). (6) Variation in the level of expression of some Tf variants thus falling under the detection limit; similarly, an unequal expression of some combined Tf alleles was reported in the horse (18).…”
Section: Discussionmentioning
confidence: 99%